Creating the Appropriate Social and Economic Conditions for the Development of Agriculture: An Investigation into the Prospects for Engaging Young Specialists - Shakibaevna Bauer, Maira; Tolegen, Zamira; Nugmankizi Mursalova, Khalima; Shakerbekovna Baidalina, Gaukhar; Telgosinovna Bekbossynova, Lyailya; ., . (International Journal of Engineering and Technology, 2018)
This paper shares the findings from a study into issues related to attracting highly qualified specialists into the nationâ€™s agricultural sector.Â Â